Pelaksanaan Kurikulum 2013 pada Bidang Studi Matematika di Sekolah Menengah Pertama Negeri (SMPN) Kota Pekanbaru Tahun Pelajaran 2016/2017 - Susda Heleni; Zulkarnain Zulkarnain (Al-Khwarizmi : Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2017)
This study aims to (1) Determine the implementation of curriculum 2013 in Mathematics on SMPN of Pekanbaru, the academic year 2016/2017. (2) Knowing what obstacles faced by Mathematics teachers SMPN of Pekanbaru in the implementation of kurikulm 2013. This study is a qualitative descriptive study, which describes the implementation of the curriculum 2013 by Mathematics teachers of SMPN Pekanbaru and the constraints they face. Subjects in this study are Mathematics teachers in SMPN Pekanbaru that implementing the curriculum 2013, such as SMP 1, SMP 6 and SMP 23 Pekanbaru. The data collection by conducting surveillance documents, and interviews with Mathematics teachers. Based on data analysis, learning process based curriculum 2013 in Pekanbaru SMP has not gone well. There are some problems in the implementation of the curriculum 2013 at SMPN Pekanbaru such as, (1) Teacher have a problem to making Student Activity Sheet; (2) Lack of teacher knowledge about models, strategies, or approach about student-centered learning; and (3) Lack of understanding about the assessment of teachers especially skills assessment.